Internal Corporate Governance and the COVID-19 Pandemic: Does It Mitigate or Intensify Earnings Management in East Africa? - SWAI, JANETH PATRICK (Universitas Airlangga, 2026)
Abstract This study examine whether internal corporate governance mechanisms- specifically board attributes and ownership structure, mitigate or intensify accrual-based earnings management (AEM) during the COVID-19 pandemic. Using hand-collected data from annual reports of non-financial listed firms in Kenya and Tanzania from 2017 to 2022, the study compares firm’s AEM behaviour in the pre-pandemic (2017–2019) and pandemic (2020–2022) periods. A panel regression model with interaction terms is employed to assess how the pandemic moderated the relationship between governance mechanisms and AEM. The results show that under normal conditions (before COVID-19), managerial ownership is associated with less AEM, suggesting reduced manipulation due to interest alignment. However, during the pandemic, managerial ownership exhibited a positive and significant interaction with COVID-19, indicating intensified earnings management, likely driven by uncertainty and the need to signal stability. Foreign ownership was associated with higher AEM during the pandemic, possibly due to reduced oversight, while board attributes had no significant impact on AEM, suggesting their limited effectiveness during pandemic periods. Thus emphasizing on context-dependent nature of corporate governance and highlighting how pandemics can reshape the influence of various corporate governance mechanisms on a firm's financial reporting behaviour. Keywords: COVID-19 pandemic; Accrual-based Earnings Management, Internal Corporate Governance Mechanisms.